1986
DOI: 10.1073/pnas.83.11.4021
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and functional effects of prenatal and postnatal omega 3 fatty acid deficiency on retina and brain in rhesus monkeys.

Abstract: Docosahexaenoic acid [22:6w3;7,10,13,16,19)] is the major polyunsaturated fatty acid in the photoreceptor membranes of the retina and in cerebral gray matter. It must be obtained either from the diet or by synthesis from other w3 fatty acids, chiefly a-linolenic acid (18:3w3). We tested the effect of dietary w3 fatty acid deprivation during gestation and postnatal development upon the fatty acid composition of the retina and cerebral cortex and upon visual function. Rhesus monkeys (Macaca mulatta) were fed sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
416
0
6

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 788 publications
(438 citation statements)
references
References 15 publications
16
416
0
6
Order By: Relevance
“…It is not possible to determine whether genotype or dietary management played the more critical role in lowering plasma acylcarnitines in this data set, because subjects who had ÎČ-subunit mutations also had among the lowest dietary LCFA intakes and the highest MCT intakes for all the participants. DHA (C22:6n−3) supplementation has been shown to elevate previously reduced plasma DHA levels to the normal range and improve visual acuity as measured behaviorally or by VEP in both rhesus monkeys and human infants [31][32][33][34]. Increased levels of n−3 fatty acid were also correlated with improved ERG parameters including an increased R max and a decreased log K in preterm infants [35], whereas n−3 deficiency produces ERG abnormalities in several animal models [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…It is not possible to determine whether genotype or dietary management played the more critical role in lowering plasma acylcarnitines in this data set, because subjects who had ÎČ-subunit mutations also had among the lowest dietary LCFA intakes and the highest MCT intakes for all the participants. DHA (C22:6n−3) supplementation has been shown to elevate previously reduced plasma DHA levels to the normal range and improve visual acuity as measured behaviorally or by VEP in both rhesus monkeys and human infants [31][32][33][34]. Increased levels of n−3 fatty acid were also correlated with improved ERG parameters including an increased R max and a decreased log K in preterm infants [35], whereas n−3 deficiency produces ERG abnormalities in several animal models [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the fetus appears to be largely protected against substantial shifts in maternal dietary fatty acid intake. Nevertheless, the reduced n-3 LCPUFA transfer to the fetuses of cafeteria-fed dams may still have significant implications for fetal development given the critical role of the n-3 LCPUFA in the neurodevelopment and immune function in the perinatal period [27,28].…”
Section: Maternal Cafeteria Feeding and Offspring Fatty Acid Statusmentioning
confidence: 99%
“…However, for the sake of clarity, only 9 separate fatty acids and 11 fatty acid combinations are reported (see Table 2a). The following indexes were calculated: EFA-index ( (n-3 n-6)a (n-9 n-7) (Hornstra et al, 1992), EFA-deÂźciency index (20 : 3n-9a20 : 4n-6) (Holman, 1960), DHADI (docosahexaenoic acid deÂźciency index : 22 : 5n-6a22 : 4n-6) (Holman, 1986;Neuringer et al, 1986) and DHASI (docosahexaenoic acid sufÂźciency index : 22 : 6n-3a22 : 5n-6) .…”
Section: Discussionmentioning
confidence: 99%
“…They found no differences in retinal DHA between breastfed and formula-fed infants, in spite of differences in DHA levels in RBC PL. However, there are animal studies in which dietary manipulation showed to have large effects on DHA content of retinal phospholipids of rhesus monkeys (Neuringer et al, 1986), guinea pigs (Weisinger et al, 1995), rats (Suh et al, 1996) and felines (Pawlosky et al, 1997). Unfortunately, in these studies, the fatty acid values in plasma and RBC were not measured and no breastfeeding group was included to compare with.…”
Section: Discussionmentioning
confidence: 99%